Effect of environmental degradation on mechanical properties of kenaf/polyethylene terephthalate fiber reinforced polyoxymethylene hybrid Composite - Zaki Abdullah, M. (2013)
The main objective of this research is to investigate the effect of environmental degradation on the mechanical properties of kenaf/PET fiber reinforced POM hybrid composite. Kenaf and PET fibers were selected as reinforcements because of their good mechanical properties and resistance to photodegradation. The test samples were produced by compression molding. The samples were exposed to moisture, water spray, and ultraviolet penetration in an accelerated weathering chamber for 672 hours. The tensile strength of the long fiber POM/kenaf (80/20) composite dropped by 50 from 127.8 to 64.8 MPa while that of the hybrid composite dropped by only 2 from 73.8 to 72.5 MPa. This suggests that the hybrid composite had higher resistance to tensile strength than the POM/kenaf composite. Similarly, the results of flexural and impact strengths also revealed that the hybrid composite showed less degradation compared to the kenaf fiber composite. The results of the investigation revealed that the hybrid composite had better retention of mechanical properties than that of the kenaf fiber composites and may be suitable for outdoor application in the automotive industry. Â© 2013 Mohamad Zaki Abdullah et al.